A validity study of the SSP-School Inclusion Questionnaire - DIANA DĂMEAN (Journal of Social Research & Policy, 2012)
The paper is based on the results of a research that aimed to identify the factors influencing school inclusion among disadvantagedstudents. The main outcome of the research was the development of the SSP-School Inclusion Questionnaire, intended to: (1)measure school inclusion levels among students; (2) identify students with significantly lower levels of school inclusion, whoneed to be included in intervention programs; and (3) measure the impact of intervention programs using subjective indicators(beneficiaries’ perception of school and teachers, feelings of safety in school, school performance). The questionnaire was completedby 480 vocational school students aged 15-19 from a large developed urban area (Cluj-Napoca) in Romania. The purpose of theresearch was to test the validity and reliability of the instrument and to propose it to professionals working in education (schoolpsychologists, school counsellors etc.) for efficient data collection and for measuring the impact of educational intervention.